Measurement of community literature development index in North Sumatera in 2021 - Dumora Jenny Margaretha Siagian; Poppy Marulita Hutagalung; Jonny Sitorus; Ceria Aprilliana (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
The literacy level of the people has a vertical relationship to the quality of a nation. A person's high interest in reading affects a person's insight, mentality and behavior. This study aims to describe the measurement results of the Community Literacy Development Index in North Sumatra in 2021, identify and analyze the obstacles faced, and provide recommendations that libraries can do in increasing the community literacy development index in North Sumatra. The urgency of this research, among others, is an effort to meet the availability of accurate and holistic data for all types of libraries, both aspects of collections, service personnel, users, library members and the existence of a budget as the basis for policy formulation as well as library development in North Sumatra. The research method in this study is quantitative research with a descriptive approach. Collecting research data using documentation studies, and questionnaires. Analysis of research data using descriptive statistical analysis. The results of the study found that the Community Literacy Development Index in North Sumatra at 12.40 was in the sufficient category. Meanwhile, there were six aspects that were found to be obstacles faced by libraries in North Sumatra in increasing the Community Literacy Development Index, namely institutional aspects, funding aspects, human resources aspects, facilities/infrastructure aspects, collection materials aspects, and reading interest aspects. Then from these six aspects, 15 strategy recommendations were made to strengthen the role of libraries in increasing the index of community literacy development in North Sumatra. Keywords: Literacy, Community Literacy Development Index, Library